Academic Burnout and Its Association with Sleep Quality, Physical Activity, and Social Media Addiction Among University Students in Perak, Malaysia: A Cross-Sectional Study - Joanne Lim, Kai Eng; Cheah, Khang Jin; Abdul Latif, Farzana Athirah; Mohd Shahrin, Fatin Izzaty (Makara Journal of Health Research, 2025)
Background: Academic burnout among Malaysian undergraduates is a rising concern, driven by academic pressure and compounded by lifestyle and behavioural factors. This study aimed to examine the associations between academic burnout, sleep quality, physical activity, and social media addiction. Methods: A cross-sectional study involving 382 undergraduate students was conducted using an online survey to collect the data. The chi-square test was used to assess bivariate associations, and multivariable logistic regression was employed to identify independent predictors of academic burnout. Results: The majority of respondents were aged 21 to 23 years (59.7%) and female (60.7%). Overall, 56.0% of respondents experienced academic burnout, with poor sleep quality highly prevalent (90.1%), 52.4% classified as minimally active, and 92.9% not meeting the criteria for social media addiction. Sleep quality was significantly associated with academic burnout in both the bivariate chi-square analysis (p = 0.030) and logistic regression analysis (p = 0.039). No significant associations were found between physical activity or social media addiction with academic burnout. Conclusions: Poor sleep quality and a minimally active level of physical activity were prevalent among university students, with sleep quality showed a significant association with academic burnout. Further research is needed to elucidate additional contributing factors and support the development of effective health promotion strategies in university settings.